A Force-Feedback Exoskeleton for Upper-Limb Rehabilitation in Virtual Reality - Antonio Frisoli; Fabio Salsedo; Massimo Bergamasco; Bruno Rossi; Maria C. Carboncini (Applied Bionics and Biomechanics)
This paper presents the design and the clinical validation of an upper-limb force-feedback exoskeleton, the L-EXOS, for robotic-assisted rehabilitation in virtual reality (VR). The L-EXOS is a five degrees of freedom exoskeleton with a wearable structure and anthropomorphic workspace that can cover the full range of motion of human arm. A specific VR application focused on the reaching task was developed and evaluated on a group of eight post-stroke patients, to assess the efficacy of the system for the rehabilitation of upper limb. The evaluation showed a significant reduction of the performance error in the reaching task (paired t-test, p < 0.02)